MENUMBUHKAN SEMANGAT MODERASI BERAGAMA DITENGAH ANCAMAN RADIKALISME - Rodiatam Mardiah Hasibuan (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2020)
Religion is inseparable from culture and customs with diversity, it is necessary to have Educational Function, Rescue Function, Supervisory Function, Function of fostering brotherhood, Transformative Function. Religious moderation in Indonesia is a middle ground to face the threat of radicalism because religious moderation in Indonesia stems from three parts, namely culture, faith, and religion. Culture, faith, and religion are integrated in Indonesian society, so that each other has a connection. This situation we encounter at formal and non-formal events. The research method used is library study. This study discusses the understanding of Religious Moderation and Radicalism. Radicalism in the name of religion can be eradicated through cultural awareness, understanding and practice of Pancasila and the NKRI Community. a moderate and inclusive Islam. Religious moderation can be shown through tawazun (balanced), i'tidal (straight and firm), tasamuh (tolerance), musawah (egalitarian), shura (deliberation), ishlah (reform), aulawiyah (prioritizing the priority), tathawwur wa ibtikar.